2005
DOI: 10.1177/0042085905278019
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Mistrust, Academic Outcome Expectations, and Outcome Values among African American Adolescent Men

Abstract: This study measured the relationship between outcome expectations, outcome value, and cultural mistrust among African American male high school students (N = 75) attending an urban, Southern California school. We hypothesized that a negative perception of the dominant culture would negatively affect academic outcome expectations and academic achievement values. The results indicated, as hypothesized, a significant inverse relationship between cultural mistrust and outcome expectations. There was also a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…Prior research (Irving & Hudley, 2005) found that low income high school adolescents' perceptions of institutional racism relate to lower expectations to gain access to the opportunity structure, regardless of their academic efforts. Similarly, low income college students, who have perhaps attended less advantaged schools or lived in poorly resourced neighborhoods, might also hold lower expectations of material reward for educational efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research (Irving & Hudley, 2005) found that low income high school adolescents' perceptions of institutional racism relate to lower expectations to gain access to the opportunity structure, regardless of their academic efforts. Similarly, low income college students, who have perhaps attended less advantaged schools or lived in poorly resourced neighborhoods, might also hold lower expectations of material reward for educational efforts.…”
Section: Discussionmentioning
confidence: 99%
“…As well, the ethnic composition of the racially identified Black student subsample was not reported, clearly demonstrating the need for nuanced examinations of within-group variability among monolithically described Black samples. Research on low-income, non-immigrant Black male high school students' beliefs about school success (Irving & Hudley, 2005) found that students who perceived their academic opportunities to be limited also expressed negative expectations about the future benefits of educational success. Expectations for economic benefits of a college education appear to diverge by immigration history and social class.…”
Section: Ijep -International Journal Of Educational Psychology 5(3) 229mentioning
confidence: 99%
See 1 more Smart Citation
“…Involuntary minority youth may expect life opportunities to be suppressed by racial discrimination in social and employment spheres rather than facilitated by educational preparation (Irving & Hudley, 2005), a perspective that somewhat diminishes academic motivation and success in high school (Irving & Hudley, 2008). Even academically successful non-immigrant Black college students attributed negative future outcomes to discrimination, although attributions were significantly more pessimistic for students in the third year of college and beyond (van Laar, 2001).…”
Section: Theoretical Explanations For Differential Academic Successmentioning
confidence: 99%
“…A significant body of research suggests that, among African American adolescents, commitment to educational and career pursuits is also influenced by adolescent racial identity attitudes (Fordham & Ogbu, 1986;Spencer, Dupree, & Hartman, 1997;Noguera, 2001Noguera, ,2008Sellers, Copeland-Lindner, Martin, & Lewis, 2006;Irving & Hudley, 2005;Fryer, 2006). A common component of most racial identity theories describes strategies employed by African Americans to cope with negative reference group orientations, with many of the coping strategies employed assumed to result in unproductive or self-limiting behaviors.…”
mentioning
confidence: 99%